Career Commitment among Bank Employees in Kathmandu Valley - Pandey , Kamana; Dahal, Subhadra (The Management Review, 2026)
The study is conducted to invest the interrelationship between affective, normative, and continuance components of career commitment and to examine their combined effect on overall career commitment among banking professionals in Kathmandu Valley. The study used three component models of Meyer and Allen’s to achieve the objective of the study by using quantitative research design and the data were collected from the structured questionnaires and distributed to the banking employees of the Kathmandu Valley, out of 120 questionnaires only 109 were valid responded. The findings from Pearson correlation and multiple regression analyses showed that affective and normative commitments significantly and positively impact overall career commitment, where the affective commitment is considered as the strongest predictor among three. In contrast, continuance commitment results show less impact on overall commitment. The results of the study suggested that emotional attachment and the important factors play a more important role in long-term career dedication than cost-related obligations, which emphasize the importance of fostering a supportive, value-driven work culture to enhance employee commitment and retention in Nepal’s banking sector.